Analisis Sebaran Kasus TB Paru BTA Positif di Kota Semarang Tahun 2018 berdasarkan Suhu Udara - Yulia Aryanti; Suhartono Suhartono; Nikie Astorina Yunita Dewanti (Jurnal Kesehatan Masyarakat, 2019)
In 2016, There were 351,893 cases found in Indonesia. The highest number of this case could be seen in Central Java. The Data obtained from the Public Health Departement of Semarang according to the first to the third quarter of 2018 shown that there were 819 people suffer from Tuberculosis. Risk factor and the pattern of this spread of pulmonary TB disease in Semarang not yet to be known. This research aims to spatially analyze the incidence distribution of positive smear Pulmonary Tuberculosis, indoor air temperature and population density in 2018 in Semarang using GIS. The research design is observational descriptive with using survey as the method. Its sample selected by using total sampling technique, with incidence variable of positive smear Pulmonary Tuberculosis, temperature and population density. The Data collected by using GPS and Thermohygrometer, which then mapped into the Geographic Information System. Result of the research is There are 203 respondent (91%) who didn’t meet the average room temperature (<18OC and > 30OC) in each sub district. The average room temperature, the respondent often used, is 32.81OC with standard deviation 1.9. The conclusion is Spatial Analysis described that the average room temperature don’t meet the eligible health regulation (>30OC) and population density has a risk of affecting positive smear Pulmonary Tuberculosis.